Great answers to tough interview questions - Yate, Martin John (Kogan Page, 2017)
With over 5 million copies sold around the world, Great Answers to Tough Interview Questions is the essential guide for all job-seekers, offering advice on writing a CV, mastering interview techniques and answering really challenging questions
Description based on publisher supplied metadata and other sources
Keywords: Employment interviewing; Job hunting; Bewerbung; Vorstellungsgespräch; Ratgeber